Development of fertilizer recommendation for cabbage production in Low Ganges River Floodplain of Bangladesh - Quddus, A F M Ruhul; Ahmed, Selim; Kamrozzaman, M M; Ahmmed, Md Motasim; Sarker, Rumpa (Fundamental and Applied Agriculture, 2017)
The study was conducted during rabi season of 2013-14 and 2014-15 at the farmer’s field of Farming System Research and Development (FSRD) site, Hatgobindapur, Faridpur under On-Farm Research Division (OFRD), Bangladesh Agricultural Research Institute (BARI) to evaluate the perfor- mance of chemical fertilizers for maximum yield of cabbage and higher eco- nomic return. The experiment was laid out in Randomized Complete Block Design (RCBD) with five dispersed replications. The experiment consisted of eight treatments viz. N242P120K33S19Zn1.4B0.6 kg ha−1 (100% NPKSZnB from Soil Test Based (STB) dose, T1), T1+25% N (T2), T1+25% NP (T3), T1+25% NK (T4), T1+25% PK (T5), T1+25% NPK (T6), 75% of T1 (T7), and native nutrient (control, T8). The treatment 100% NPKSZnB (soil test based) and additional 25% NPK (T6) treatment produced maximum head yield of cabbage (78.89 t ha−1) which was statistically identical with 100% soil test based NPKSZnB (T1), 100% NPKSZnB with additional 25% N (T2), 100% NPKSZnB with additional 25% NP (T3) and 100% NPKSZnB with additional 25% NK (T4) treatments. The lowest head yield (33.92 t ha−1) was obtained from native nutrient (control). The highest gross margin (Tk 756,093 ha−1) was obtained from T6 (100% NPKSZnB from STB with additional 25% NPK) followed by T2 (T1 with additional 25% N) and T1 treatments. The results indicated that, the marginal rate of return (MRR) of changing from T7 to T1 was 1818% (for every Tk 100 of additional investment Tk 1,818 was obtained) and a changing from T1 to T2 gave MRR of 319%. From the experimental results, it was concluded that application of 100% chemical fertilizers of N242P120K33S19Zn1.4B0.6 kg ha−1 from soil test based (T1) would be suitable for higher yield and eco- nomic return of cabbage production in calcareous soil under Low Ganges River Floodplain (Agroecological Zone 12).